The Economic Reform Process in Russia - Odling-Smee, John.; Lorie, Henri (Washington, D.C. : International Monetary Fund, 1993)
Although various factors point to a more arduous and longer transition in Russia than in Eastern Europe, the broad policy approach should be similar. A necessary condition for effective macroeconomic stabilization is the imposition of hard budget constraints on enterprises. Financial assistance from the Government and the central bank to enterprises must be strictly controlled to ensure compatibility with both inflation objectives and the creation of incentives for reform. While Russia needs external financial assistance, it must be willing and able to pursue economic policies that ensure that the assistance has the desired effects, especially macroeconomic stability and systemic reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Government; Liberalization; Market Economy; WP; Russian Federation